TO MATHEMATICAL PREDICTION OF FLOOD WATER - Олійник, Андрій Петрович; Клапоущак, Оксана Ігорівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The prediction of flood waters level has been made based on the Dni- ester and Tisza example for 2013 and 2014 taking to account the statistics from automatic hydrological stations using a mathematical model.